Dopamine Receptors: Is It Possible to Become a Therapeutic Target for Depression? - Zhao, Fangyi; Cheng, Ziqian; Piao, Jingjing; Cui, Ranji; Li, Bingjin (Frontiers in Pharmacology, 2022)
Dopamine and its receptors are currently recognized targets for the treatment of several neuropsychiatric disorders, including Parkinson’s disease, schizophrenia, some drug use addictions, as well as depression. Dopamine receptors are widely distributed in various regions of the brain, but their role and exact contribution to neuropsychiatric diseases has not yet been thoroughly studied. Based on the types of dopamine receptors and their distribution in different brain regions, this paper reviews the current research status of the molecular, cellular and circuit mechanisms of dopamine and its receptors involved in depression. Multiple lines of investigation of these mechanisms provide a new future direction for understanding the etiology and treatment of depression and potential new targets for antidepressant treatments.